English language proficiency of affirmative students in graduate courses from the perspective of Freire's unprecedented-viable (Revista Contexto & Educação, 2025)
English education is a privilege accessible to few in society. The primary aim of this position paper is to reflect upon and discuss the English language proficiency of graduate students admitted through affirmative action policies at federal universities (affirmative students) and also we will question the use and/or the lack of using English language. To do so, we begin by discussing the process of internationalization in higher education (Knight, 2004) and the demand for English proficiency. We then address the dominance of English over other languages as a strong indication of coloniality and modernity ((Mignolo, 2019; Quijano, 1993; Quintero; Figueira; Elizalde, 2019). Finally, we open a dialogue on overcoming these barriers through Paulo Freire's perspective of the "inédito-viável." (1992). We conclude that by thinking, willing, and acting in response to a limiting situation, we can initiate a decolonial project, denaturalizing what has been naturalized and engaging collectively in the search for alternatives to transform the problem.
Keywords: English Language Proficiency; Internalization; Decoloniality; Unprecedented-viable